Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
[tex]x = -2 +2\sqrt 3\\\\x = -2 -2\sqrt 3[/tex]
Step by step explanation:
[tex]~~~~~~x^2 +4x +4 = 12\\\\\implies x^2 +2\cdot 2x + 2^2 = 12\\ \\\implies (x+2)^2 = 12\\\\\implies x +2 = \pm\sqrt{12}\\\\\implies x = -2 \pm\sqrt{12}\\\\\implies x = -2\pm\sqrt{4 \times 3}\\\\\implies x = -2 \pm2\sqrt 3[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.